A DESCRIPTION STUDY OF NURSING STUDENTS IN CLINICAL PRACTICE - Marlina, Theresia Titin (Universitas Respati Yogyakarta, 2017)
Background: Nursing clinical practice is a learning process in order to give nursing services bypracticing as nurses in the clinical setting. The students practiced nursing process approach, andperformed the attitude, behavior, and skills in a professional manner.Objective: The aim of this studyis to describe of medical-surgical the nursing students in clinical practice which includes preparation,guidance, role models, opportunities to apply science and behavioral transformation. Methods : Thiswas survey study that conducted in a private nursing academic in Yogyakarta. A questionnaire wasused to describe the preparation, mentoring, role models, opportunities to apply science and behaviortransformation in clinical practices. The participants were informed concented and selected usingpurposive sampling with inclusion criteria for the 3rd semester student who just completed the firstnursing clinical practice, l7-20 years old and willing to become respondents. Ninty eight studentswere taken as samples. Descriptive statistic with the presentage were used. Results: 54.5% studentsstated that the explanation of nursing clinical practice is quite clear, while 27.3 % stated that it wasclear enough, 58.4% students said that their instructor gave a very good guidance, while 54.5% saidthat the instructor gave them average level of guidance, 88.2% said that there were sufficient numberof patients available to achieve the target of competence, and 76.2% said that they achieve thecompetence level above the target. 98.7% of students said that they had a nurse role model thatpossess a professional behaviour, attitude, and skills, 57.1% of the stated that they could apply thetheory in real setting. Conclusion: Implementation of nursing clinical practice of students in privatenursing academy in Yogyakarta has done well, with clear learning objectives delivery, properguidance, many practice opportunities, enough cases availability and good role model acquired bystudents during the practice.